2004
DOI: 10.1111/j.1523-1755.2004.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of mast cells in the development of renal fibrosis: Use of mast cell–deficient rats

Abstract: Role of mast cells in the development of renal fibrosis: Use of mast cell-deficient rats.Background. Recent clinical studies have shown that the number of interstitial mast cells increases in various types of renal disease and correlates well with the magnitude of interstitial fibrosis. The present study was conducted to assess the role of mast cells in renal fibrosis by examining an experimental glomerular disease.Methods. A rat model of chronic glomerular disease, puromycin aminonucleoside-nephrosis, was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 41 publications
4
43
0
2
Order By: Relevance
“…Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58). Thus, the potential therapeutic value of mast cell manipulation in fibrosis is uncertain (23,59).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58). Thus, the potential therapeutic value of mast cell manipulation in fibrosis is uncertain (23,59).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%
“…In vitro experiments showed that heparin inhibited the expression of mRNA encoding TGF-␤ in cultured rat fibroblasts. 91 Preliminary studies in a murine model of ureteral obstruction also suggested that mast cells protect against fibrosis. 92 Thus, data from experimental mast cell-deficient mice do not support the attractive hypothesis that mast cells play a profibrotic role in chronic renal disease.…”
Section: Experimental Studies Exploring the Role Of Mast Cells In Renmentioning
confidence: 99%
“…In pristane-induced experimental lupus nephritis, mast cell-deficient mice developed equivalent renal disease to WT mice (27). A slightly protective role for mast cells in the development of fibrosis was suggested in rats 6 wk after the induction of puromycin aminonucleoside nephritis (28). A functional role of mast cells in the pathogenesis of crescentic GN has not been established.…”
mentioning
confidence: 99%